Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

How do I solve this trig identity: cos2x/(1+sinx^2)=tan(pie/4 -x)

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SEE EXPERT ANSWER

To see the expert answer you'll need to create a free account at Brainly

i think ur question is cos2x/(1+sin2x) now cos2x =cos^2x -sin^2x=(cosx+sinx)(cosx-sinx) and 1+sin2x = cos^2x + sin^2x +2sinxcosx =(cosx+sinx)^2 thus cos2x/(1+sinx)^2= (cosx+sinx)(cosx-sinx)/(cosx+sinx)^2 =(cosx- sinx)/((cosx+sinx) divide both num and denom by cosx and then we have =(1-sinx/cosx)/(1+sinx/cosx) =(1-tanx)/(1+tanx) = (tan(pi/4) -tanx)/(1+tan(pi/4)tanx)=tan(pie/4 -x)
for the second last step.. where did the square roots go? isnt it suppose to be: (1-sinx/cosx)(1-sinx/cos)/(1+sinx/cos)(1+sinx/cosx)
actually the factors (cosx+sinx) are there both in num and denom hence they cancel each other

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

but its (cosx-sinx) in the num :s
(cosx+sinx)(cosx-sinx) / (cosx+sinx)^2 =(cosx-sinx) / (cosx+sinx)
i hope its clear now
why 13 u hv included in ur id ? if u don't mind
if its (cosx+sinx)^2, it has to equal (cosx+sinx)(cosx+sinx)
idk random.
(cosx+sinx)^2= (cosx+sinx)(cosx+sinx) (correct ) that is why one of the (cosx+sinx)
cancel each other
how does cos^2x -sin^2x=(cosx+sinx)(cosx-sinx)
USE ..A*A -B*B =(A)^2 -(B)^2 = (A+B)(A-B)...
okay, then why isnt :(cosx+sinx)^2 --> (cosx-sinx)(cosx+sinx)
bcoz a^2 =a*a
so (a+b)^2 =(a+b)(a+b)
but if u multiply (a+b)(a-b) u get (a^2 -b^2)
so (a^2-b^2) does not equal (a-b)^2 ?
sahi hai..
oh i get it..
=(1-tanx)/(1+tanx) = (tan(pi/4) -tanx)/(1+tan(pi/4)tanx)=tan(pie/4 -x) can u explain that? .. where did pi/4 come from ?
Tan (pi/4) = 1.
is that a trig identity?
No. If you do that on a calculator you get that.
Tan(pi/4) is always 1. Look on a unit circle.
Okay, thanks!!
Welcome :) .

Not the answer you are looking for?

Search for more explanations.

Ask your own question